Development of an Informal Reading Inventory for Senior High School: A Preliminary Study - Cainoy, John Philip; Teodoro, Ana Liza; Marvilla, Jacquie Bamba (International Journal of Language and Literary Studies, 2024)
This preliminary study addresses the urgent need for an Informal Reading Inventory (IRI) specifically designed for Senior High School (SHS) students in the Philippines. National assessments have highlighted significant deficiencies in reading proficiency, prompting the Department of Education (DepEd) to implement comprehensive reading initiatives. However, the absence of a specialized assessment tool for SHS students presents a critical gap. This study proposes a Test Design Statement for developing an IRI that aligns with Grades 11 and 12 curriculum competencies, international standards (CEFR B2 and C1 levels), and the linguistic profile of Filipino students. The proposed IRI aims to assess essential reading skills, facilitating targeted interventions and supporting the overall goal of producing proficient, independent readers. The study outlines a comprehensive evaluation plan focusing on reliability, validity, authenticity, interactiveness, and practicality, emphasizing the necessity for institutional support and collaboration.